Konsep demokrasi dan inovasi dalam pendidikan - Maulidya, Baiq fina Fadhila; siti rofiqa, siti rofiqa (Maliki Interdisciplinary Journal, 2025)
Democratic education gives everyone the opportunity to participate in high-quality education in accordance with the principles of justice and active involvement. Meanwhile, educational innovation focuses on developing creative ideas and utilizing technology to enhance education and learning experience. Successful innovation is characterized by clear objectives, effective implementation in schools, and measurable impact. This article also outlines the significance of both concepts in improving the quality of education, developing students’ potential, and building a generation capable of actively contributing to democratic and social life. In this context, the synergy between educational democracy and innovation is key to creating an inclusive, adaptive, and student-centered learning system. Democracy ensures equal learning opportunities for every individual, while innovation offers new approaches that foster creativity, independence, and competitiveness in the global era. Both complement each other in shaping a dynamic and sustainable education ecosystem.